Assessment of litter production and decomposition rate of selected mangrove species in Paraiso Eco Learning Park, San Jose Tacloban City, Leyte - Lopez, Myrabelle B. (2022)
Mangrove forests are highly productive ecosystems that provide nutritional sustenance accessed by diverse aquatic resources. Their nutrient pool of organic matter is attributed to its production of litterfall and its decomposition. The present study constitutes the first assessment of the dynamics of mangrove litter production and decomposition of two predominant mangrove species: Avicennia marina and Rhizophora apiculata in Paraiso Eco Learning Park, San Jose Tacloban City, Leyte. The study was conducted for two months as affected by rainy season (November-December 2021) and dry season (February-March 2022) at two stations (landward and seaward) which are separately inhabited by the said species. Rhizophora apiculata in the seaward area produced higher litterfall (3.00 g/meter square/month out of the total average of 4.60 g/meter square/month. Vegetative structures, particularly the leaves account for 87.98% of the produced litter in both species. Temperature, PH, humidity, rainfall, and wind speed showed strongly positive correlation with litterfall production, but only humidity has shown significant association (r squared= 0.960; p < 0.05). Faster decomposition was recorded by R. apiculata with a remaining dry weight of 2.52% (rainy season) and 5.14% (dry season). Only salinity exerted strong positive association to leaf decomposition. The rainy season documented the greatest production and rapid degradation of litter that may be ascribed to increased rainfall, leading to the shedding of vegetative components which promotes nutrient uptake and cycle. Lastly, statistical results indicated significant differences in litter production with respect to zonation (p=0.02) and seasonality (p= 0.05), while decomposition rate was shown to be relatively similar between zonations and seasons.